Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content:1. Methods of measuring migration - Irbid Governorate as a modelMrs. Ibtisam “Mahmoud Amin” Marie , Prof. Nazih Ibrahim Almanasieh2. The study of motives and the Issues of Mixed Marriages in Saudi Arabia: An Inductive Analytical Approach in Literature ReviewLecturer \ Munirah A. Alduraywish3. Situational Awareness towards Enhancing the Quality of Life for Rural Women in Some Villages in Zefta Center, Gharbia GovernorateDr. Rabab Selim Elserafy4. The sustainability of the types of floors used within the spaces of temporary housing in the Hajj seasonMrs. Najwa Nasser Al-Hazmi5. The criminal and social effects of electronic games "A comparative legal jurisprudence study in the light of Saudi law and Islamic law"Dr. Abdu Ali Muhammad Al-Jedi6. Evaluation of the Knowledge Sharing Process on the Ministry of Education Website in The Kingdom of Saudi Arabia: A Case StudyDr. Mona Ali Mahnabi7. Publishing policies in open access journals: A literature reviewMr. Fahad Saad Alnasser8. A Critical Reading of the Major Introductions to understanding the West and its Determinants A systematic attempt to establish the OccidentalismProf. Abdul Aziz Fodil BOUCHAIR
Keywords: Journal of Humanities & Social Sciences